Comparing the log‐response curve and adsorption isotherm model for removing dissolved organic matter during La Nina event. (13th July 2020) - Murshed, Mohamad Fared; Mohammadpour, Reza; Chow, Christopher
Abstract: Coagulation is the most commonly used chemical treatment process that is used to remove contaminants from drinking water. In this study, the Log‐Dose‐Response (LDR) model and theoretical isotherm models (Langmuir and Freundlich) were employed to predict the DOC removal in the coagulation process during La Nina events. The six months water samples were collected during an intense La Niña cycle at various locations along the River Murray and elsewhere in South Australia. The Jar testing was conducted with different Alum dose and pH levels, that is, at 5.5, 6.0 and 7.0. The result indicates that the optimum dose of Alum for DOC removal is 15.0 mg/L and the LDR model is the best one for predicting the DOC removal in the coagulation process. The mean of standard error for this model is less than 5% for all pHs compared to Langmuir and Freundlich predictions with a value of 11% and 8%, respectively. Moreover, the standard deviation for the LDR model was low at 2.49, 1.22 and 0.75 for pH 5.5, pH 6.0 and pH 7.0, respectively.